NUTRITIONAL MANAGEMENT OF PAEDIATRIC PATIENTS AFTER ORGAN, BONE MARROW OR HAEMATOPOIETIC STEM CELL TRANSPLANTATION - Manca Čot; Anija Orel; Tomaž Poredoš; Andreja Širca Čampa; Evgen Benedik (The Society for Children with Metabolic Disorders, 2024)
Nutritional support measures for paediatric patients who have undergone organ, bone marrow, or hematopoietic stem cell transplantation need to be implemented to prevent infection during immunosuppressive therapy and to speed up recovery after the procedure. Children undergoing immunosuppressive therapy are at high risk of infection. Typical examples of foods with a high risk of infection are raw and uncooked foods. Special care should be taken to maintain an adequate nutritional status and provide all the nutrients and energy necessary for the child's growth and development, which will also improve recovery. It is essential to educate healthcare workers, kitchen staff and parents on proper hygiene, safe handling of high-risk foods and appropriate food preparation based on existing microbiological food safety guidelines.